The Convergence of Maqasid Shari’a and Pancasila in Strengthening the Spirit of Nationalism in Indonesia - Moh Nur Fauzi (Universitas Nurul Jadid, 2023)
This article describes the convergence between maqasid shari’a and Pancasila to develop the spirit of nationalism. This research is descriptive qualitative and can be categorized into the type of library research. Various data and sources were obtained from various literatures related to the concept of maqasid shari’a and Pancasila which were associated with nationalism. The research method used is a literature review. The data comes from books, scientific journals, national media and website that relevant to the topic. The focus of the research is directed at, first, the theoretical and methodological description of the maqasid shari’a concept; second, a description of the nature of nationalism, and third, searching for common ground between the concepts of maqasid shari’a and Pancasila in the frame of diversity. From this study it was found that first, the concept of maqasid shari’a occupies an urgent and significant position as a theoretical and methodological tool in observing the plural and pluralistic reality of Indonesia; second, nationalism is an important ideology in an effort to unite a plural and multicultural Indonesia with various ethnicities, tribes, cultures, languages, beliefs and religions, third, there is a meeting point or convergence between the concepts of maqasid shari’a and Pancasila substantively and inherently in the concept of Pancasila which is the great creations of this nation's founder.